Association of Interleukin-6 Levels with Body Mass Index in Chronic Obstructive Pulmonary Disease Patients - Seema Gupta; Varinder Saini; Shivani Jaswal; Jasbinder Kaur; Shristi Krishna; Manpreet Kaur (Indian Journal of Respiratory Care)
Background: Chronic obstructive pulmonary disease (COPD) is considered to be a systemic inflammatory state. There is an increase in the circulating markers of inflammation like interleukin-6 (IL-6), tumor necrosis factor-alpha, and C-reactive protein (CRP) in COPD patients, which are reported to be associated with disease severity. IL-6 levels are found to be increased in overweight/obesity as well. However, increased body mass index (BMI) has been documented to show a protective effect on COPD. The current study was planned to explore the association of IL-6 with BMI and grades of disease severity. Materials and methods: The study design was observational and cross-sectional and included 70 diagnosed cases of COPD. The patients were divided into underweight, normal weight, and overweight/obese groups by Asian criteria based on BMI. The circulating IL-6 and CRP levels were measured. The disease severity was assessed by the Global Initiative for COPD criteria. Results: No significant difference was found in IL-6 and CRP levels among different subgroups based on BMI (p > 0.05). However, a statistically significant difference was found in IL-6 and CRP levels among patients with mild, moderate, and severe disease (p < 0.001). A significant correlation was found between IL-6 and CRP, but no significant correlation was found between these and BMI. Conclusion: The present study does not support the obesity paradox in COPD, as no significant association of BMI with disease severity was found, whereas IL-6 and CRP showed a significant difference among patients with different severity grades.